Model Aplikasi Pembelajaran Menghapal al-Qur'an Berbasis Android - Yudihartanti, Yulia; Rizki, Ahmad; Ariannor, Wahyudi; Noor, Muhrian (STMIK Banjarbaru, 2024)
This research details the problems at the Tahfidz Al-Hasan House, where students do not memorize the Quran frequently outside study hours due to the use of cell phones. To address this issue, an independent muroja'ah-based Android application was developed with monitoring and rote assessment features. The development method employs the ADDIE model, known for its effectiveness in designing learning applications. The test results indicate that the application functions well, making a positive contribution to improving Quran memorization skills. This research encourages further exploration of online learning, responsive to the needs of the Muslim millennial generation. An in-depth evaluation of the application model can serve as the basis for further development, enhancing the effectiveness of technology-based Quran memorization learning.Keywords: Murojaah; ADDIE Model; Memorization; Quranic Education; Online LearningÂ Â AbstrakPenelitian ini merinci permasalahan di Rumah Tahfidz Al-Hasan, di mana santri kurang melakukan pengulangan hafalan Al-Quran di luar jam belajar akibat penggunaan ponsel. Untuk mengatasi masalah tersebut, dikembangkan aplikasi Android berbasis muroja'ah mandiri dengan fitur monitoring dan penilaian hafalan. Metode pengembangan menggunakan model ADDIE, yang efektif dalam merancang aplikasi pembelajaran. Hasil pengujian menunjukkan aplikasi berfungsi baik, memberikan kontribusi positif dalam meningkatkan kemampuan menghafal Al-Quran. Penelitian ini mendorong eksplorasi lebih lanjut mengenai pembelajaran online dan responsif terhadap kebutuhan generasi milenial Muslim. Evaluasi mendalam terhadap model aplikasi dapat menjadi dasar untuk pengembangan lebih lanjut, meningkatkan efektivitas pembelajaran menghafal Al-Quran berbasis teknologi. Â